KUALITAS PELAYANAN BAGI PASIEN RAWAT INAP PESERTA BPJS DI RSUD. PROF W. Z.JOHANNES KUPANG - Hendrik Toda (Universitas Nusa Cendana, 2019)
This study aims to reveal social phenomena related to the quality of care for patients of BPJS members in Prof. W. Z Johannes. By using a qualitative approach so that it will get more indepth answers regarding the quality of service at the Prof. W.Z. Johannes hospital. Theory of Service Quality is used from Parasuraman, et al (1990), which is described in five dimensions: Tangible, Reliability, Responsiveness, Assurance and Empathy. By using interview techniques with patients and informants as well as researchers' observations of hospital services in hospitals. Prof. W. Z Johannes. The result of the study shows Tangible dimensions related to the appearance of doctors and nurses, the appearance of physical facilities, other supporting facilities are good enough but the atmosphere in the room and around the patient room is less comfortable. The dimensions of Reliability are good enough to be proven by the ability of medical personnel to provide services quickly when patients need it. Responsivennes dimension which the ability of health personnel is able to respond to complaints of patients at the time of first treatment until the action in the inpatient room. The service Assurance dimension is related to the availability of a large number of medical personnel but not proportional to the number of patients. Given the number of patients who use services in Prof. W. Z Johannes is quite a lot not only BPJS patients but there are also general patients and patients who use hospitals other insurance. The dimension of Empathy is service provided through hospital values by not discriminating on the patient's social status. Keywords: Service Quality, Inpatient Patients, BPJS Participants, Prof. W.Z Johannes hospital